An Analysis of the Influence of Financial Ratios on Stock Prices of Energy and Mining Companies Listed on the Indonesia Stock Exchange - REZA ANGGIDYA PUTRI; AZILA PUTRI JELITA (Journal of Strategic Behaviour Accounting, 2025)
This study is designed to explore the impact of financial ratios on stock values of companies in the energy and mining sectors listed on the Indonesia Stock Exchange (IDX) during the period of 2021–2024. The financial ratios examined include the Current Ratio (CR), Total Asset Turnover (TATO), and Return on Assets (ROA). This research employs a descriptive quantitative approach using multiple linear regression analysis. The findings reveal that individually, ROA has a significant influence on stock values, while CR and TATO show no significant effect. However, when analyzed simultaneously, the three ratios collectively exert a significant impact on stock values, contributing 24.6%. These results confirm that profitability is the dominant factor considered by investors in determining stock prices within the energy and mining sectors. The study is expected to contribute to the development of financial knowledge and serve as a useful reference for investors in making investment decisions. Keywords: Current Ratio, Total Asset Turnover, Return on Assets, stock price, energy, mining, Indonesia Stock Exchange.